Dietary supplementation of nano-selenium eliminates the negative effects of long-term ivermectin injection on growth and reproductive performance of female rabbits (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: We investigated the effects of a source of selenium [inorganic or nano-selenium (nano-Se)] on female V-line rabbits with or without injection of ivermectin (IVM). Material and Methods: Eighty-four rabbits (12 weeks old) were randomly divided into 4 groups of 21 rabbits each with the basal diet supplemented as per the following treatments: G1 (control): inorganic Se at 0.3 mg/kg diet with no IVM injection; G2: inorganic Se with IVM injection; G3: nano-Se with no IVM injection; and G4: nano-Se with IVM injection. IVM was injected subcutaneously at 0.2 mg/kg body weight starting when the does were 14 weeks old and repeated weekly for five consecutive weeks. Results: Replacement of inorganic Se with nano-Se improved body weight and total body weight gain, total feed intake, average feed conversion ratio, and reproductive performance (age at puberty, number of service/conceptions, conception rate, number of kits/litter, and litter weight at birth). Similarly, sexual activity of does, serum estrogen levels, and serum levels of antioxidants (glutathione reduced, catalase, and malondialdehyde) increased in nano-Se-supplemented groups. Ivermectin treatment in inorganic Se-supplemented groups was detrimental to growth and reproductive performance, while these parameters improved in IVM-treated and nano-Se-supplemented groups. Conclusion: Nano-Se mitigated the negative effects of IVM treatment on the growth and reproductive performance of does.J. Adv. Vet. Anim. Res., 9(1): 128–137, March 2022http://doi.org/10.5455/javar.2022.i577